Excess in Moderation: General Anesthesia for Cesarean Delivery. Issue 1 (March 2016) - Hawkins, J.L.
Abstract : ( Anesth Analg . 2015;120:1175–1177) This editorial comments upon a national survey on current anesthesia practices for cesarean deliveries in the Czech Republic, abstracted above by Stourac et al. One of the main findings of the survey was that general anesthesia was administered in 44.4% of cesarean deliveries. Although the authors of the report indicated that this high rate of usage could be an indicator of lower quality health care, the author of this editorial questions whether this percentage is a reliable indicator, as there is no current evidence-based method to determine a preferable rate for general anesthesia in this context. The ideal rate for general anesthesia for cesarean delivery is unknown.